Pengembangan Media Edukasi Diriku untuk Mengatasi Masalah Pubertas Siswi Madrasah Ibtidaiyah Al Ma'arif 03 Langlang Singosari - Putri, Rona Sari Mahaji; Sari, Nila Kartika (Universitas Baiturrahim, 2025)
Many adolescent girls (female students) are not ready and do not understand what happens when entering puberty. Puberty is one of the periods that a person goes through before adolescence. Various changes occur, but are often not understood by adolescents. Lack of knowledge will have an impact on the attitudes and behavior of early adolescents in responding to various things during puberty. Sexual education during puberty is often considered taboo by adolescents, so it tends to be less noticed and discussed. It takes a health education that is easy for adolescents to understand, acceptable and unconsciously provides benefits for adolescents. The purpose of the research is to make educational media